Children composing, 4-14 - Glover, Joanna (Routledge/Falmer, 2000)
Composing is part if the mainstream music curriculum for many children yet children's music does not receive the same attention as their art or creative writing. Children Composing 4-14 traces the ways in which composing can be organised and taught within the school music curriculum, drawing on children's own music-making activities. This practical book looks at how teaching composing can enable hildren to progress by acquiring musical skills and understanding, whilst developing their own sense of musical purpose. One of the main concern's of the book is the need to sustain continuity.